2017
DOI: 10.1364/optica.4.001209
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot multispectral imaging with a monochromatic camera

Abstract: Multispectral imaging plays an important role in many applications from astronomical imaging, earth observation to biomedical imaging. However, the current technologies are complex with multiple alignment-sensitive components, predetermined spatial and spectral parameters by manufactures. Here, we demonstrate a single-shot multispectral imaging technique that gives flexibility to end-users with a very simple optical setup, thank to spatial correlation and spectral decorrelation of speckle patterns. These seemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(78 citation statements)
references
References 32 publications
0
74
0
Order By: Relevance
“…More recently, with the knowledge of the point spread function (PSF) measured before data acquisition [40], Zhuang et al showed high speed full-color imaging through a diffuser [41]. Several other deconvolution experiments have been reported [42][43][44] which require the measurement of PSF in advance. Recently, Antipa et al demonstrated the reconstruction of light field and digital refocus from the caustics pattern caused by a phase diffuser [45].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, with the knowledge of the point spread function (PSF) measured before data acquisition [40], Zhuang et al showed high speed full-color imaging through a diffuser [41]. Several other deconvolution experiments have been reported [42][43][44] which require the measurement of PSF in advance. Recently, Antipa et al demonstrated the reconstruction of light field and digital refocus from the caustics pattern caused by a phase diffuser [45].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its application is restricted in fields such as ultra-fast imaging [60,61]. Recently, remarkable snap-shot spectral imaging techniques have been widely developed to acquire a 3D spectral data-cube in just a single exposure [62][63][64][65][66]. However, since the correlation between pixels and wavelengths of the 3D image data-cube is not utilized in these methods, the information acquisition efficiency is lower than the Shannon limit [67,68].…”
Section: Gisc Spectral Cameramentioning
confidence: 99%
“…For conventional imaging technologies, which is based on the point-to-point correspondence between the object and the image planes, the resolution can be accurately analyzed with the transmission function of the imaging systems [103,104]. However, for imaging systems based on the wavefront random phase modulation [20,64,[105][106][107][108], since the point-to-point correspondence doesn't exist anymore, their resolution ability is difficult to be directly obtained from the transmission function, but can be obtained by analyzing the high-order correlation of light fields. Based on high-order spatial autocorrelation of thermal light, a lensless Wiener-Khinchin telescope was proposed [22].…”
Section: Lensless Wiener-khinchin Telescopementioning
confidence: 99%
“…However, the wavefront shaping techniques are time-consuming, due to the required long sequence of measurement steps, one for each imaging pixel, and are thus difficult to use without feedback. A recent breakthrough approach by S. K. Sahoo et al [15], which exploits the decorrelations of spectral point spread functions (sPSF) [13,14], has achieved multispectral imaging and color imaging by deconvolution technique. However, this technique suffers from some shortcomings of the decorrelations bandwidth and deconvolution technique: (i) requires measuring the sPSF before imaging; and (ii) the image quality is predetermined by the stability of the optical components.…”
Section: Introductionmentioning
confidence: 99%